Pengembangan Delta Lakkang Sebagai Kawasan Ekowisata di Kota Makassar - Angga Armansyah; Mukti Ali; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Delta Lakkang has the potential in the field of tourism which includes natural potential in the form of the location and condition of its land function, socio-cultural potential in the form of language life patterns and architecture typical of traditional houses, as well as historical potential in the form of Japanese heritage bunkers from the results of World War II. The determination of the ecotourism concept for the Lakkang Delta region is based on the Makassar City Regional Regulation concerning the 2015-2035 Regional Tourism Development Master Plan (RIPPDA). The application of Delta Lakkang is a leading ecotourism destination in Makassar, namely by knowing the existing conditions of potential and existing problems based on observations and interviews. This study aims to identify the potential and problems contained in the Lakkang Delta Region and compile planning directions that will be carried out in the Lakkang Delta region. The analysis techniques used are spatial analysis, ODTW analysis, photo mapping analysis, and SWOT analysis using IFAS and EFAS methods. From the results of the study note that the strategy is in quadrant II, namely the direction of Aggressive Maintenance Strategy (aggressive improvement strategy) or internal consolidation strategy with development priority lies in the WO strategy including completing various types of tourism support facilities in order to attract tourists, provide various kinds of training and understanding to the people who will be directly involved in tourism activities, providing easy access and smoothness to the Lakkang Delta region, utilizing technological advancements to carry out promotion as a comprehensive tourism area.